解方程 log4 (3x-1)=log4 (x-1)+log4 (3+x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 11:40:45
解方程log4(3x-1)=log4(x-1)+log4(3+x)解方程log4(3x-1)=log4(x-1)+log4(3+x)解方程log4(3x-1)=log4(x-1)+log4(3+x)l
解方程 log4 (3x-1)=log4 (x-1)+log4 (3+x)
解方程 log4 (3x-1)=log4 (x-1)+log4 (3+x)
解方程 log4 (3x-1)=log4 (x-1)+log4 (3+x)
log4 (3x-1)=log4 (x-1)+log4 (3+x)
log4 (3x-1)=log4[(x-1)(3+x)]
3x-1=x²+2x-3
x²-x-2=0
(x+1)(x-2)=0
x=-1,x=2
真数大于0
x=-1、x-1
log4(3x-1)=log4((x-1)×(3+x))
3x-1=x2+2x-3
x2-x-2=0
x=2,x=-1
取x=2
解方程log4 x+1/log4 x=10/3
解方程 log4 (3x-1)=log4 (x-1)+log4 (3+x)
解方程log4(3x+1)=log4x+log4(3+x)
解方程log4(3x+1)=log4x+log4(3+x).会的帮帮忙,
解方程:log2(3-x) - log4(x+5) =1
解方程log4(3-x)+log0.25(3+x)=log4(1-x)+log0.25(2x+1)
解方程log4(3x+1)=log4x+log(3+x)最后是log4(3+x)
log4(3x-1)-log4(3+x)=log4(x-1)
解方程log4(2-x)=log2(x-1)-1
解方程log1/2[log4(x^2-1)]=1
方程log2(x-1)=log4(3-x)的解集~~~
解方程log4(3*2^x+7)=log2(2^x+1)
解方程 log2(x^2-3)=2log4(6x-10)-1等于2
解方程:log2(x²-3)=2log4(6x-10)-1
解方程 log2(x^2-3)=2log4(6x-10)-1
解方程:log4{2log3[1+log2(1+3log2 x)]}=1/2
解方程log2(2x)*log4(x/4)=2
对数方程 log2(x+1)-log4(x+4)=1